2012
DOI: 10.1017/s0033291712001031
|View full text |Cite
|
Sign up to set email alerts
|

Poor attention rather than hyperactivity/impulsivity predicts academic achievement in very preterm and full-term adolescents

Abstract: (2013) Poor attention rather than hyperactivity/impulsivity predicts academic achievement in very preterm and full-term adolescents. Psychological Medicine, Vol.43 (No.1). pp. 183-196. ISSN 0033-2917 Permanent WRAP url: http://wrap.warwick.ac.uk/52783/ Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
110
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 67 publications
(106 reference statements)
7
110
1
3
Order By: Relevance
“…Firstly, child behavior during a challenging cognitive assessment lasting 1 h 20 min was evaluated by psychologists with the Tester's Rating of Child Behavior (TRCB) Task Orientation index scale (Cronbach's α =.85; subscale inter-rater reliabilities ICC (intra-class correlation coefficient) =.63 to .97) [3]. Secondly, child attention across the whole assessment day was evaluated as a consensus rating by the whole research team (TEAM rating of psychologist, assistant psychologist, and pediatrician, α =.98) [3]. These two attention ratings correlated highly with each other (r=.62, p<0.01) and were thus z-scored and combined into a single scale of attention regulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, child behavior during a challenging cognitive assessment lasting 1 h 20 min was evaluated by psychologists with the Tester's Rating of Child Behavior (TRCB) Task Orientation index scale (Cronbach's α =.85; subscale inter-rater reliabilities ICC (intra-class correlation coefficient) =.63 to .97) [3]. Secondly, child attention across the whole assessment day was evaluated as a consensus rating by the whole research team (TEAM rating of psychologist, assistant psychologist, and pediatrician, α =.98) [3]. These two attention ratings correlated highly with each other (r=.62, p<0.01) and were thus z-scored and combined into a single scale of attention regulation.…”
Section: Methodsmentioning
confidence: 99%
“…Preterm birth increases the risk for attention difficulties [1][2][3][4] as well as long-term academic underachievement [3,5,6]. Studies have suggested that early self-control abilities (e.g.…”
mentioning
confidence: 99%
“…First, the assistant psychologist rated children's behaviour during a cognitive assessment that lasted on average 80 minutes using the Tester Ratings of Child Behaviour (TRCB (1,27)). Six of 13 items were combined to create a Task Orientation subscale including attention, robustness/endurance, demandingness (reversed score), cooperativeness, compliance and difficulty (reversed score).…”
Section: Methodsmentioning
confidence: 99%
“…Second, adapting a consensus model, the whole research team (psychologist, assistant psychologist and paediatrician) evaluated children's behaviour based on their observations during the whole assessment day. They rated children's behaviours using three items of the TRCB: attention, robustness/endurance and demandingness (reversed score) (1). An index score of attention Attention problems and gestational age 6 was computed using the Team ratings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation